White Emitters by Tuning the Excited‐State Intramolecular Proton‐Transfer Fluorescence Emission in 2‐(2′‐Hydroxybenzofuran)benzoxazole Dyes. Issue 40 (21st August 2014) - Benelhadj, Karima; Muzuzu, Wenziz; Massue, Julien; Retailleau, Pascal; Charaf‐Eddin, Azzam; Laurent, Adèle D.; Jacquemin, Denis; Ulrich, Gilles; Ziessel, Raymond
Abstract The synthesis, structural, and photophysical properties of a new series of original dyes based on 2‐(2′‐hydroxybenzofuran)benzoxazole (HBBO) is reported. Upon photoexcitation, these dyes exhibit intense dual fluorescence with contribution from the enol (E*) and the keto (K*) emission, with K* being formed through excited‐state intramolecular proton transfer (ESIPT). We show that the ratio of emission intensity E*/K* can be fine‐tuned by judiciously decorating the molecular core with electron‐donating or ‐attracting substituents. Push–pull dyes 9 and 10 functionalized by a strong donor (nNBu2) and a strong acceptor group (CF3 and CN, respectively) exhibit intense dual emission, particularly in apolar solvents such as cyclohexane in which the maximum wavelength of the two bands is the more strongly separated. Moreover, all dyes exhibit strong solid‐state dual emission in a KBr matrix and polymer films with enhanced quantum yields reaching up to 54 %. A wise selection of substituents led to white emission both in solution and in the solid state. Finally, these experimental results were analyzed by time‐dependent density functional theory (TD‐DFT) calculations, which confirm that, on the one hand, only E* and K* emission are present (no rotamer) and, on the other hand, the relative free energies of the two tautomers in the excited state guide the ratio of the E*/K* emission intensities.